On the Gas-Phase Hydrogenation of E110 Zirconium Alloy with a Chromium Coating; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 18 - Kudiyarov V. N. Victor Nikolaevich; Lomygin A. D. Anton Dmitrievich; Sidelev D. V. Dmitry Vladimirovich; Kruglyakov M. A. Mark Aleksandrovich (2024, 2024)
Title screen